Competency Requirements for HR Employees Working Remotely - Krasnova, Anna (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2021)
Objective: To present the competency requirements for employees in HR departments providing their work remotely. Research Design & Methods: Qualitative research was conducted using content analysis. The research sample consisted of advertisements for remote work for positions related to HRM. Findings: The study shows that most employers looking for remote-based HR employees require candidates to have qualifications necessary for remote work, which are the least required hard (technical) competencies. Implications / Recommendations: Remote work is becoming a standard form of work, and requires employees to have additional competences to make them more effective. In order to create effective virtual teams, employers should take into account the competency requirements necessary for remote work at the recruitment stage. Contribution: The list of universal competences for remote work presented in the article can be used by employers to define the requirements for candidates for various positions, and as a source of knowledge when constructing research tools to measure competencies for remote work.